Cancer-Associated circRNA–miRNA–mRNA Regulatory Networks: A Meta-Analysis - Khan, Shaheerah; Jha, Atimukta; Panda, Amaresh C.; Dixit, Anshuman (Frontiers in Molecular Biosciences, 2021)
Recent advances in sequencing technologies and the discovery of noncoding RNAs (ncRNAs) have provided new insights into the molecular pathogenesis of cancers. Several studies have implicated the role of ncRNAs, including microRNAs, long noncoding RNAs (lncRNAs), and recently discovered circular RNAs (circRNAs) in tumorigenesis and metastasis. Unlike linear RNAs, circRNAs are highly stable, closed-loop RNA molecules. It has been established that circRNAs regulate gene expression by controlling the functions of microRNAs (miRNA), RNA-binding protein (RBP), or by translating into proteins. CircRNA-miRNA-mRNA regulatory axis is associated with human diseases, such as cancers, Alzheimer’s, and diabetes. Here, we explored the interaction between circular RNAs, microRNAs, and their target genes in various cancers using state-of-the-art bioinformatics tools. We identified differentially expressed circRNAs, miRNAs, and mRNAs on multiple cancers from publicly available data. Furthermore, we identified many crucial driver and tumor suppressor genes in the circRNA-miRNA-mRNA regulatory axis, in various cancers. Together, our data provide a deeper understanding of the circRNA-miRNA-mRNA regulatory mechanisms in cancers.